Fragment‐Based Stabilizers of Protein–Protein Interactions through Imine‐Based Tethering. Issue 48 (25th September 2020) - Wolter, Madita; Valenti, Dario; Cossar, Peter J.; Levy, Laura M.; Hristeva, Stanimira; Genski, Thorsten; Hoffmann, Torsten; Brunsveld, Luc; Tzalis, Dimitrios; Ottmann, Christian
Abstract: Small‐molecule stabilization of protein–protein interactions (PPIs) is a promising concept in drug discovery, however the question how to identify or design chemical starting points in a "bottom‐up" approach is largely unanswered. We report a novel concept for identifying initial chemical matter for PPI stabilization based on imine‐forming fragments. The imine bond offers a covalent anchor for site‐directed fragment targeting, whereas its transient nature enables efficient analysis of structure–activity relationships. This bond enables fragment identification and optimisation using protein crystallography. We report novel fragments that bind specifically to a lysine at the PPI interface of the p65‐subunit‐derived peptide of NF‐κB with the adapter protein 14‐3‐3. Those fragments that subsequently establish contacts with the p65‐derived peptide, rather than with 14‐3‐3, efficiently stabilize the 14‐3‐3/p65 complex and offer novel starting points for molecular glues. Abstract : A novel concept for optimizing orthosteric protein–protein interaction (PPI) stabilization is reported. Increasing interactions with the protein partner that contributes less to the composite binding pocket of the stabilizer (NF‐κB, red surface) results in increased stabilization, whereas further enhancing the interaction with the dominant partner protein (14‐3‐3, white surface) does not contribute to the stabilizing effect.